Digital Religious Engagement in Relation to Anxiety and Depression in Adults: A Systematic Review - Ilham Tazakam Hakam Wirosa; Syarifah Rose Pandanwangi; Widodo Sarjana A.S (IJIP : Indonesian Journal of Islamic Psychology, 2026)
Anxiety and depression are common mental health conditions that substantially affect quality of life. Religious and spiritual engagement has been associated with selected mental health outcomes in conventional offline settings, but the role of digital religious engagement remains unclear. This systematic review aimed to examine digital religious engagement in relation to anxiety and depression in adults. A literature search was conducted in Medline, Scopus, PubMed, and the Cochrane Library for studies published from January 2015 to May 2025. Eligible studies examined religious or spiritual engagement delivered, facilitated, or accessed through digital platforms and reported anxiety and/or depression outcomes. Risk of bias was assessed using design-specific tools, and findings were synthesized narratively because of substantial heterogeneity. Of 400 records identified, 6 studies met the inclusion criteria. Some studies reported potentially beneficial associations between digital religious engagement and selected mental health outcomes, including lower odds of anxiety or depression, reduced emotional burden, and reduced depressive symptoms. However, findings were inconsistent across outcomes, populations, and study designs, and some studies reported null or mixed results. Spiritual support appeared relevant to some observed associations, particularly in relation to depression, but the current evidence remains insufficient to support firm mechanistic conclusions. Overall, digital religious engagement may be associated with selected mental health benefits in some contexts, but the available evidence remains limited and heterogeneous. More rigorous longitudinal and controlled studies are needed.